Exposure of chitosan to UV/ozone: Structural information and antibacterial activity - Osiris W. Guirguis, Gehan T. El-Bassyouni, Mona A. Esawy, Nada R. Abd Elkader, Hadeer M. Mahmoud, Hend M. Mostafa, Nabawia A. Abdel-Zaher (Journal of Applied Pharmaceutical Science, 2016)
In the present work, variation in the group coordination of chitosan due to the exposure to UV/ozone was considered by the FTIR reflectance. Pronounced variations in the intensities of reflectance bands and shifts in their positions were detected. This could be attributed to the change in the molecular configuration of chitosan. On the other hand, the well diffusion method was used to investigate the anti-bactericidal activities against two common bacterial strains Bacillus subtitles (B. subtilis) and Escherichia coli (E. coli)] by detecting the mean inhibition zone diameters (IZD) against the microorganisms. The achieved data revealed that the chitosan exposed to UV/ozone confirmed a high potential of antibacterial activity.
Keywords: Chitosan, Structural information , FTIR, Antibacterial activity, UV/ozone treatment.